Development of New Medical Device – Investment Evaluation - Petra MARESOVA; Lukas PETER; Martin MATEJICEK; Jan MACI; Kamil KUCA (Communications of International Proceedings, 2020)
The entrance of company into the regulated market for medical devices is associated with compliance with many regulations, ordinances and laws. On the other hand, the production and sale of medical devices is very promising, in all economic periods. In May 2021, Europe is facing a major change in the legislation on medical devices in the form of MDR Directive 2017/745, which has been developed to protect patients in order to increase their safety. This is undoubtedly the right and proportionate situation for society, but it involves high costs and investments for manufacturers. Companies are now faced with the question of what future economic result can be expected and what strategy to follow. The goal of this study is to suggest and specify steps of medical device development for economic evaluation and calculation of economic efficiency. For these purposes, a calculator that calculates economic efficiency indicators such as Return on Investment, Net Present Value and Breakeven Point, was made. It takes into account the new legislative conditions, and it also allows its users to set the risk class and other characteristics of the medical device. The study also contains demonstrated calculation of economic efficiency indicators for one case study.
Keywords: Medical Device; Development; Economic Efficiency; Investment.